Increased Risk of Metabolic Syndrome in Antidepressants Users: A Mini Review - Gramaglia, Carla; Gambaro, Eleonora; Bartolomei, Giuseppe; Camera, Paolo; Chiarelli-Serra, Maira; Lorenzini, Luca; Zeppegno, Patrizia (Frontiers in Psychiatry, 2018)
Mounting evidence has shown that the risk of metabolic syndrome (MetS) is substantially overlapping in the diagnostic subgroups of psychiatric disorders. While it is widely acknowledged that patients receiving antipsychotic medications are at higher risk of MetS than antipsychotic-naive ones, the association between antidepressants and MetS is still debated. The goal of our mini review was to analyze the relationship among depressive symptoms, antidepressant use and the occurrence of MetS. Adhering to PRISMA guidelines, we searched MEDLINE, reference lists and journals, using the following search string: ((("Mental Disorders"[Mesh]) AND "Metabolic Syndrome"[Mesh]) AND "Antidepressive Agents"[Mesh]), and retrieved 36 records. Two reviewers independently assessed records and the mini review eventually included the data extracted from 8 studies. The Newcastle-Ottawa Scale was used to assess the quality of the selected studies. Overall, the results of the mini review seem to support the association among depressive symptoms, antidepressants therapy and MetS. Except for H1-R high-affinity ones, the relationship between antidepressants and MetS still needs to be clarified. Considering the widespread prescription of antidepressants, both on behalf of psychiatrists and primary care physicians, further research on this topic is recommended.